EVALUASI STATUS MUTU AIR DANAU RAWAPENING - Agatha Sih Piranti; Diana Retna Utarini Suci Rahayu; Gentur Waluyo (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Increasing type and number of human activities will impact on decreasing quality of water. Therefore, it is necessary to determine the water quality status of Rawapening Lake regularly to ensure that the water quality remains in its natural condition. The purposes of this study were to evaluate the water quality status and class of Rawapening Lake. The survey was done in the lake during dry season for 3 months (July to September 2016). Water sampling conducted in seven locations. The measured variables were all parameters as specified in Government Regulation No. 82 of 2001. To determine the water quality status was using storet methods. Determination of the water class was by comparing the concentration of all parameters with the standard. Observations indicated that the Rawapening Lake water quality status was in heavily polluted. There were eight parameters exceeding the standard i.e. TSS, BOD, COD, total phosphor and total coliform, Cd and Pb, and H2S. Therefore, it is necessary to decrease them through activities such as not throwing rubbish into the lake, lifting biomass of water hyacinth, picking up peat soil sediments, using environmentally friendly fuels, reducing fertilizers and pellet, reforesting critical lands, limiting mining activities, banning waste disposal directly to rivers.